2016
DOI: 10.1166/jnn.2016.13603
|View full text |Cite
|
Sign up to set email alerts
|

Etch Characteristics of SiO2 Using Pulsed Triple-Frequency for Ar/C4F6/O2 Capacitive Coupled Plasmas

Abstract: We investigated the effects of 13.56 MHz radio frequency (rf) power as a medium frequency power on the plasma characteristics and etch properties of an amorphous carbon layer (ACL) and SiO 2 , using Ar/C 4 F 6 /O 2 gas mixtures in a capacitively coupled plasma (CCP) system operated with pulsed superimposed triple-frequency power of 60 MHz (source)/13.56 MHz (bias)/2 MHz (bias). Compared to the dual frequency rf power of 13.56 MHz (400 W)/2 MHz (900 W) or 60 MHz (400 W)/2 MHz (900 W), the use of triple-frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…fluxes, densities, energies, and spatial uniformity of charged particle densities, as well as the creation of radicals), but can also cause an improvement of actual etching characteristics, e.g. the etching uniformity and rate, the anisotropic etch profile and higher etch selectivity, etc [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…fluxes, densities, energies, and spatial uniformity of charged particle densities, as well as the creation of radicals), but can also cause an improvement of actual etching characteristics, e.g. the etching uniformity and rate, the anisotropic etch profile and higher etch selectivity, etc [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Pulse bias technology, which simply ramps up the bias power, was introduced almost 10 years ago. 36,[122][123][124] In the off period of the pulse operation, the sheath collapses and the potential at the wafer surface decreases, which allows electrons and negative ions to reach the etching front, thus neutralizing the positive charge build-up. This charge neutralization helps to increase the effective bias power and suppresses the accumulation of positive charges at the hole bottom owing to the transport of negative ions during the pulse-off phase.…”
Section: Radical Transport and Ion Transport Inside Har Featuresmentioning
confidence: 99%
“…A third method, the pulsed plasma technique, is to turn the plasma on and off by modulating the RF driving voltages with pulse parameters (such as pulse frequency, duty cycle, etc) during the operation of the plasma processing. It has been reported that both improved etch selectivity and etch uniformity can be achieved, due to decreased gas dissociation and enhanced radical diffusion during pulse off time [13,14]. Meanwhile, the decreased positive ion energy and extraction of negative ions during the pulse off time are believed to play an important role in neutralizing the accumulated electrons and ions in the trenches, respectively, contributing to better control of the etching profile and critical features [9,15].…”
Section: Introductionmentioning
confidence: 99%